Використання сігма-пі нейронних мереж для розпізнавання об’ектів в реальному часі - Кулішов, Є. А. (ХНУРЕ, 2025)
In modern military conflicts, the ability to quickly identify targets plays a key role in increasing the effectiveness and safety of combat operations. Thanks to advanced technologies and advances in machine learning and big data analysis, it is possible to accurately identify enemy forces and improve strategic decision-making. However, these technologies have significant limitations that complicate their use. But -P (Sigma-Pi) neural networks can help overcome these limitations. This work aims to review the problem of increasing the speed of military object recognition using sigma-pi neural networks.
Keywords: розпізнавання об’ектів; modern military conflicts